Differences in biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) result in similar performance of seedlings of two Mediterranean oaks with contrasting leaf habit - Espelta, Josep Maria; Cortés, Pilar; Mangirón, Marta Retana (Ecoscience, 2005)
Co-occurrence of winter-deciduous and evergreen oaks is common in some Mediterranean-type climate areas. However, whether these species show an overlap in their regeneration niche is still poorly understood. We explored experimentally the changes in survival, growth, biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) in seedlings of a deciduous oak (Quercus cerrioides) and an evergreen oak (Quercus ilex) in response to co-variation in light and water availability. Quercus cerrioides exhibited higher root length, root area, leaf nitrogen content, and less negative δ13C, but lower leafiness than Q. ilex. The interaction between species and light in specific leaf area and root–shoot ratio indicated different mechanisms to overcome water stress in the two oaks, with Q. ilex relying on leaf hardening and Q. cerrioides relying on a high root–shoot ratio. However, the two species showed similar survival and growth in most of the light–water gradient. Ecological inference of these results indicates that seedlings of these species have a similar ability to cope with variations in light and water in spite of their contrasting leaf habit. This similar performance suggests a competition for similar micro-sites during establishment, rather than a partitioning of the regeneration niche.
Keywords: deciduous; evergreen; Mediterranean-type climate; Quercus cerrioides; Quercus ilex; Regeneration

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens

The impact of grazing on forage quality of the herbaceous vegetation in the Mamora cork oak forest, Morocco - Alami, M. Mejjati; Bedell, T. E.; Sharrow, S. H.; Berkat, O. (African Journal of Range & Forage Science, 1997)
This research was conducted in the Mamora cork oak forest of Morocco to describe the impacts of sheep grazing (no use, 35% use, 70% use) in March, April, May and June of 1987 and 1988 on seasonal changes in forage quality of the herbaceous vegetation. The study showed that trends in herbage quality were related mainly to plant maturity. As more species mature, forage quality declines and falls below animal nutritional requirements, especially for young animals. With declining forage quality, the manager has the option of moving stock to areas of less-mature forage, supplementing the forage or modifying the demand placed upon it.
doi: 10.1080/10220119.1997.9647913doi: 10.1080/10220119.1997.9647913The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: crude protein; IVOMD; Mediterranean-type climate; minerals; time of grazing